Transition from the classroom to online educational environment: First impressions - Lameski, Petre; Bidikov, Vladislav; Kjiroski, Kiril; Jakimovski, Boro; CHorbev, Ivan; Zdravevski, Eftim; Trajkovikj, Vladimir (Faculty of Computer Science and Engineering, Ss. Cyril and Methodius University in Skopje, Macedonia, 2020)
With the world pandemic caused by the COVID19 virus, the lectures at the Faculty of Computer Science and Engineering (FCSE), at the Ss. Cyril and Methodius University in Skopje, Republic of North Macedonia, were fully transferred online within the first week of the start of the imposed movement and public gathering limitations by the Government of North Macedonia. After two weeks of the start of the classes, we performed a survey for both students and faculty teaching staff to gather the initial sentiment for the online classes and to identify opinions, suggestions for best practices and possible obstacles. In this paper, we present the technological solutions used to give the lectures and the results of the initial surveys.
Keywords: distance learning, moodle, e-learning, online education